Haematological, serum biochemical and hormonal profile in West African Dwarf goats during pregnancy - Shittu Olalekan Oluseyi; Okwelum Ngozi; Famakinde Samuel Ayodele; Odeyemi Adebisi Joshua; Toviesi Dedewanu Peter (Agricultura Tropica et Subtropica, 2023)
The haematological attributes during pregnancy assumed new importance when it was realised that pregnancy is a form of physiological stress and hormones appear to be involved in the process of pregnancy and parturition. Hence, an experiment aimed at assessing and determining the haematological, biochemical and hormonal profile during pregnancy was conducted for five (5) months using twelve (12) artificially inseminated female West African Dwarf goats aged 2 – 4 years with live weights ranging from 15 to 26 kg. Does were raised semi‑intensively throughout the duration of the experiment. Blood was collected once a month for haematological, biochemical and hormonal analysis. Data obtained were analysed by the method of least squares analysis of variance (SAS, 2003) using a general linear model appropriate for a completely randomised design. The gestation period had a highly significant (p < 0.001) effect on red blood cell (RBC) and white blood cell (WBC) counts. Cholesterol and glucose were significantly (p < 0.001) affected by the gestation period, similar to the cortisol and progesterone profile (p < 0.001).